Infestation of Glycaspis brimblecombei Moore on Thirteen Eucalyptus Species and Their Relationship with the Chemical Composition of Essential Oils. (2nd February 2016) - Lucia, Alejandro; Naspi, Cecilia; Zerba, Eduardo; Masuh, Héctor
Abstract : Glycaspis brimblecombei is a pest insect that affects Eucalyptus genus and was firstly detected in Argentina in 2005. The main objective of this study is to determine the correlation between the level of infestation and chemical composition of essential oils extract. In an experimental plantation of 13 Eucalyptus species, the natural presence of the psyllid in the adaxial and abaxial faces of the leaves was determined and the mean number of individuals per species was calculated. The essential oils were extracted by hydrodistillation and analyzed for their chemical composition by gas chromatography-mass spectrometry. The results showed that 7 out of 13 species of Eucalyptus were not affected by G. brimblecombei : E. dunnii, E. globulus maidenii, E. globulus ssp. globulus, E. viminalis, E. cinerea, E. sideroxylon, and E. gunnii . The most affected Eucalyptus species were E. tereticornis and E. camaldulensis whereas the infestation in E. grandis × E. tereticornis and E. grandis × E. camaldulensis was intermediate. E. saligna and E. grandis were the least affected species. The relative concentrations of the compounds 1, 8-cineole and α - and β -phellandrene in the essential oils are highly correlated to the rate of infestation with G. brimblecombei .